Paradigma Filosofis Integrasi Keilmuan Berdasarkan Refleksi Historis Perguruan Tinggi Keislaman: Philosophical Paradigm of Scientific Integration Based on Historical Reflections on Islamic Higher Education - Sari, Maya (Jurnal Filsafat Indonesia, 2024)
The scientific integration paradigm is not immediately accepted and has good implications at the UIN level in PTKI. So many problems that arise in its application so this study aims to; analyze the history of PTKI in Indonesia as an effort to discover a developing scientific paradigm; analyze how the anomaly of thought began to occur; describe how the new paradigm developed and; know the implications of that paradigm. This study uses literature studies to construct analytical narratives. Thomas Khun taught about the meaning of paradigm, even though his big idea was to criticize the doctrinal truth of science. In this case the view of religious knowledge cannot be forced at all in reflecting the paradigm of scientific integration. However, Lakatos was able to offer the concept of a "Research Program" to review that religious scholarship is absolute hardcore and must be protected by falsification. Wrapped in the Protective Belt as another scientific analogy, it can be seen how the implementation of religious-based scientific integration is simply illustrated in Lakatos's philosophy.